2019
DOI: 10.1002/celc.201901688
|View full text |Cite
|
Sign up to set email alerts
|

Surface Properties of Battery Materials Elucidated Using Scanning Electrochemical Microscopy: The Case of Type I Silicon Clathrate

Abstract: Silicon clathrates have attracted interest as potential anodes for lithium‐ion batteries with unique framework structures. However, very little is known about the surface reactivity and solid electrolyte interphase (SEI) properties of clathrates. In this study, operando scanning electrochemical microscopy (SECM) is used to investigate the effect of pre‐treatment on the formation dynamics and intrinsic properties of the SEI in electrodes prepared from type I Ba8Al16Si30 silicon clathrates. Although X‐ray photoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…It has been previously shown that the SEI growth on Si clathrates can be problematic depending on the processing conditions of the clathrate. [13,18] Another potential explanation for the irreversible capacity is the trapping of Li during relaxation, which could be related to the higher polarizations found during delithiation. The hypothesis is supported by the observation that the GITT voltage profile (Figure 8e) does not show the peak labeled with the asterisk seen in the galvanostatic curve (Figure 8a), suggesting that the periods of relaxation have an effect on the delithiation pathway.…”
Section: Reversible LI Insertion In Si 136mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously shown that the SEI growth on Si clathrates can be problematic depending on the processing conditions of the clathrate. [13,18] Another potential explanation for the irreversible capacity is the trapping of Li during relaxation, which could be related to the higher polarizations found during delithiation. The hypothesis is supported by the observation that the GITT voltage profile (Figure 8e) does not show the peak labeled with the asterisk seen in the galvanostatic curve (Figure 8a), suggesting that the periods of relaxation have an effect on the delithiation pathway.…”
Section: Reversible LI Insertion In Si 136mentioning
confidence: 99%
“…Due to the large interest in Tt elements as high-capacity Li-ion battery anodes, the electrochemical properties of Tt clathrates have also been investigated in recent years, revealing properties distinct from those of diamond cubic structured analogues. [8][9][10][11][12][13][14][15][16][17][18] For instance, the reaction of Li with the type-I clathrate Ba 8 Al 16 Si 30 is dominated by surface rather than bulk reactions, [15] whereas the Ba 8 Al y Ge 46-y (0 < y < 16) clathrate undergoes bulk phase transitions to form amorphous Li-Ba-Ge phases with local structures similar to those in Li-Ge crystalline phases. [10,16] For the type-II clathrate Na 24 Si 136 , the lithiation profile is similar to that for diamond cubic Si, [12] whereas Na 1.6 Si 136 displays one more similar to that of amorphous Si.…”
mentioning
confidence: 99%
“…[8] Alternative approaches make use of a ME at fixed positions to follow the SEI formation upon potentiostatic cycling by which the lateral variation of SEI properties cannot be assessed. [9] Thus, those approaches are not suitable to follow local changes of protecting SEI properties when a charging or discharging ionic current is passed across the SEI in rechargeable Li-ion and Li metal batteries. [10,11] Recently, we introduced a setup in which SECM images are recorded after intermittent potentiodynamic charging steps by which incipient steps of SEI formation on Si electrodes were uncovered.…”
Section: Introductionmentioning
confidence: 99%
“…These set ups are based either on a fixed array of cells generated on the top (the resolution is then limited by the intercell distance, measurements can be made simultaneously on several if not all cells), [ 165,166 ] or on an X – Y moving probe that can be positioned above each point of the substrate (the resolution is limited by the diameter of the tip from tens of µm (scanning electrochemical microscopy) to mm, the probe possibly contain a reference electrode, measurements have to be conducted sequentially). [ 167 ] The rest of the physical/chemical characterizations of the materials libraries is probably less straightforward given the thin film form of the materials, their possible amorphous character, and the presence of light elements (including Li). Due to inappropriateness to the HTE approach of some techniques such as Rutherford backscattering spectrometry and nuclear reaction analysis for example, additional approaches mentioned above consisting in the combination/global processing of more or less complete, low/high accuracy sets of measurements will probably appear as a necessity and a new frontier.…”
Section: High‐throughput Experimentationmentioning
confidence: 99%
“…probe possibly contain a reference electrode, measurements have to be conducted sequentially). [167] The rest of the physical/ chemical characterizations of the materials libraries is probably less straightforward given the thin film form of the materials, their possible amorphous character, and the presence of light elements (including Li). Due to inappropriateness to the HTE approach of some techniques such as Rutherford backscattering spectrometry and nuclear reaction analysis for example, additional approaches mentioned above consisting in the combination/global processing of more or less complete, low/high accuracy sets of measurements will probably appear as a necessity and a new frontier.…”
Section: Figure 11 Schematic Diagrams Of Sequential Depositions In Co...mentioning
confidence: 99%